-7(m+3)=2(12-6m)

Simple and best practice solution for -7(m+3)=2(12-6m) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7(m+3)=2(12-6m) equation:


Simplifying
-7(m + 3) = 2(12 + -6m)

Reorder the terms:
-7(3 + m) = 2(12 + -6m)
(3 * -7 + m * -7) = 2(12 + -6m)
(-21 + -7m) = 2(12 + -6m)
-21 + -7m = (12 * 2 + -6m * 2)
-21 + -7m = (24 + -12m)

Solving
-21 + -7m = 24 + -12m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '12m' to each side of the equation.
-21 + -7m + 12m = 24 + -12m + 12m

Combine like terms: -7m + 12m = 5m
-21 + 5m = 24 + -12m + 12m

Combine like terms: -12m + 12m = 0
-21 + 5m = 24 + 0
-21 + 5m = 24

Add '21' to each side of the equation.
-21 + 21 + 5m = 24 + 21

Combine like terms: -21 + 21 = 0
0 + 5m = 24 + 21
5m = 24 + 21

Combine like terms: 24 + 21 = 45
5m = 45

Divide each side by '5'.
m = 9

Simplifying
m = 9

See similar equations:

| .15x+.05(2-x)=.10(17) | | 150s(225s-3.50)=2000 | | -2+3x=-5 | | 0=25a+2 | | 4a-5b=6b | | (2x-9)+(3x^2-5x+3)=x | | 9x+29-x-28=87 | | -1+5x=39 | | (6n-4)+14=1 | | .24(10000)-.02y=.08(y+10000) | | -15-15x=-4x-8x | | 5x-15=25y | | 2(X+4)+2=4 | | -(3x-1)= | | 2(2x-2)=-16 | | 9-2(x-3)=9 | | 5x+5(3x-7)=125 | | .30(24)+.05x=.15(12+x) | | 2d^2=8-10d | | |x+1|=0 | | X=4.5+y | | 174=22x+8+6x-2 | | (3x^2+2x-6)+(x^2-4x)=x | | 60=7x+5 | | 4y^2+5y-12=0 | | 3 = q2 | | (-1)19= | | 7(2l+5)=91 | | (3x^2+2x-6)+(x^2-4x)= | | 4x^2+4x-9= | | d+3.77-1.99=5.38 | | 10y-7=9+2 |

Equations solver categories